1997
DOI: 10.1002/(sici)1097-4695(19970605)32:6<554::aid-neu2>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal precursors of the adult rat subependymal zone persist into senescence, with no decline in spatial extent or response to BDNF

Abstract: The adult mammalian brain continues to harbor ependymal/subependymal zone (SZ) precursor cells, which can give rise to neurons in vitro. In adult rats, explants of the rostral 6–7 mm of the SZ give rise to neurons in vitro, and over this entire expanse, neuronal survival is supported specifically by brain‐derived neurotrophic factor (BDNF). We asked whether either the (a) spatial distribution, (b) abundance, or (c) BDNF responsiveness of the neuronal precursor population was affected by age. Explants of three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(37 citation statements)
references
References 51 publications
1
36
0
Order By: Relevance
“…10 B). Interestingly, several studies have demonstrated that the olfactory input modulates the expression of molecules, such as tenascin-R (Saghatelyan et al, 2004) and BDNF (McLean et al, 2001), that promote migration, differentiation, and survival of neuronal precursors arising from the SVZ (Kirschenbaum and Goldman, 1995;Goldman et al, 1997;Gascon et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…10 B). Interestingly, several studies have demonstrated that the olfactory input modulates the expression of molecules, such as tenascin-R (Saghatelyan et al, 2004) and BDNF (McLean et al, 2001), that promote migration, differentiation, and survival of neuronal precursors arising from the SVZ (Kirschenbaum and Goldman, 1995;Goldman et al, 1997;Gascon et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…92 In these experiments, BDNF appeared to enhance initial neuronal differentiation but not survival: proliferation of cells in the spheres was not affected by BDNF, and the BDNF-stimulated increase in neuron number did not persist at longer culture times. 92 However, other investigators have reported that BDNF does promote survival of neurons in SVZ explant cultures isolated from adult rats; 93,94 NGF and NT-3, however, do not appear to have this effect. 93 BDNF appears to have effects on SVZ-derived neurons in vivo as well.…”
mentioning
confidence: 94%
“…Thus, it has been shown that hippocampal neurogenesis declines with increasing age (11,(19)(20)(21)(22), and this process is related to a decline in proliferative activity rather than to a general change in metabolic conditions or an alteration of the survival of the newly born neurons (8,(19)(20)(21)23). However, whatever the role of these various relationships, a quantitative correlation between neurogenesis and performance still has not been demonstrated in a hippocampal-dependent test (24).…”
mentioning
confidence: 99%